Linguistic Landscape: A Language Learning Media in An Underdeveloped Region - Agus Riadi; Fransiska Way Warti (Indonesian TESOL Journal, 2021)
As the result of the implementation of the latest curriculum in Indonesia, namely curriculum 2013, some problematic issues have arisen in its application. The apparent facts of this are the reduced number of hours dedicated to the subject of English, and the hampered distribution of the curriculum properties in rural areas, such as textbooks and teacher training for the curriculum. To resolve this dilemma, there is a need to find another means for teachers in rural areas to teach English, for example by using the authentic and contextual English text that is dispersed in their surroundings (Linguistic Landscape). Therefore, the aims of this research are to investigate the LL as a form of English exposure that students may encounter around their school neighbourhood, and the English language teachers’ perception of LL if it is to be applied as an additional learning resource, taking as an example a school in one underdeveloped region such as in Pulau Maya, Kayong Utara-West Borneo. This research employed a qualitative method by using an educational case study to investigate the teachers and the environment of this sample school. The data were obtained in the form of photographs and interviews. From the analysis, it was found that there are abundant LL signs that could promote students’ learning of English in improving their vocabulary, pragmatic competence, multimodal literacy, grammatical features, and their understanding of social aspects. Despite some sceptical perceptions, most of the teachers also seemed to acknowledge the apparent advantages of using LL in their future teaching.